Studi Literasi Efek Stressor Pada Kualitas Kinerja Pelayanan Tenaga Kesehatan - Komet Rama Daud; Dinda Bestari; Rizki Tomi Resna Suhendar; Vip Paramarta (STIKES Columbia Asia Medan, 2023)
Health workers, as the spearhead in providing services, have a very important role in maintaining and improving the quality of life of the community. However, in carrying out their duties, health workers are often faced with various pressures and stressors which can have a significant impact on their performance. Increased service demands, high workloads, and emotional stress inherent in the work environment of health workers can be factors that trigger potentially detrimental stress. For nurses, factors that influence stress include high workloads, limited staff, work demands and responsibilities, interpersonal relationships with fellow nurses and other health workers, knowledge about caring for patients, and changes in work dynamics. The impact of stress experienced by nurses on the performance of health workers can be seen in the quality of health services and the image of the institution, in mental and physical health, in absenteeism and late work, as well as in the relationship with happiness and performance.